2021
DOI: 10.1007/s11914-021-00715-6
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Patterns in Type 1 and Type 2 Diabetes Mellitus: A Narrative Review of Recent Literature

Abstract: Purpose of Review In this narrative review, we have summarized the literature on fracture risk in T1DM and T2DM with a special focus on fracture site, time patterns, glucose-lowering drugs, and micro- and macrovascular complications. Recent Findings T1DM and T2DM were associated with an overall increased fracture risk, with preferent locations at the hip, vertebrae, humerus, and ankle in T1DM and at the hip, vertebrae, and likely humerus, distal forearm, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 92 publications
(167 reference statements)
0
15
0
Order By: Relevance
“…type 1 and type 2 diabetes (3,4), with most focusing on the total (nonspecific) fracture risks or major osteoporotic sites of the hip or vertebrae (5). Additionally, patients with type 1 and type 2 diabetes have a higher risk of postfracture complications, prolonged healing of fractures, and higher mortality after a hip fracture (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…type 1 and type 2 diabetes (3,4), with most focusing on the total (nonspecific) fracture risks or major osteoporotic sites of the hip or vertebrae (5). Additionally, patients with type 1 and type 2 diabetes have a higher risk of postfracture complications, prolonged healing of fractures, and higher mortality after a hip fracture (6,7).…”
mentioning
confidence: 99%
“…Furthermore, glucagon-like peptide 1 receptor agonists and sodium-glucose cotransport 2 inhibitors have been implemented as treatments of type 2 diabetes and are not associated with a lower bone quality or increased risk of fracture (14). Simultaneously, sulfonylureas are associated with hypoglycemia and increased fracture risk (5) and are becoming less commonly used in type 2 diabetes (15). Moreover, glycated hemoglobin levels have decreased over time in Denmark both in patients with type 1 and type 2 diabetes, suggesting that the patients have more well-regulated glycemia over time (13), which could cause fewer hypoglycemic episodes, reducing fracture risk (16).…”
mentioning
confidence: 99%
“…Numerous studies in diverse populations of children and adults have shown that people with T1D have an increased risk of fracture that is greater in magnitude than what is observed for T2D [ 38 , 39 ]. Notably, the risk of hip fracture has consistently been shown to be increased out of proportion to other skeletal sites [ 40 •, 41 ].…”
Section: Type 1 Diabetes and Bone Healthmentioning
confidence: 99%
“…Notably, NAFLD is associated with overweight and obesity, where the presence of elevated body mass index and fat content interferes with a correct estimation of bone mineralization at the dual-energy X-ray absorptiometry (DXA) scan, the gold standard technique for osteoporosis clinical assessment. Besides, increase bone fragility is described in both type 1 and type 2 diabetes mellitus (T2DM) [11]: in individuals with diabetes, qualitative impairment of bone structure and degraded micro-architecture lead to increased fracture risk in presence of normal to high bone mineral density (BMD) [12]. Thus, although in dysmetabolic individuals the evaluation of bone structure quality more than mineral density may unravel increased fragility and fracture risk, data on this regard are scarce and not available in NAFLD populations.…”
Section: Introductionmentioning
confidence: 99%